The impact of pulmonary tuberculosis on immunological and metabolic features of diabetic patients - Chen, Haijun; Su, Li; Bao, Jinhua; Zhang, Kun; Li, Yuze; Mao, Enuo (Frontiers in Immunology, 2022)
Impaired immune responses have been observed in patients with type-2 diabetes mellitus (T2DM), which increases susceptibility to tuberculosis infection. However, the effect of the tuberculosis infection on the immunological and metabolic features of T2DM is largely unknown. To investigate this question, age- and sex-matched patients with pulmonary tuberculosis (PTB), T2DM, or T2DM combined with PTB were recruited from the Infectious Disease Hospital of Heilongjiang Province between January and September 2020. Healthy subjects were used as controls. Cytokines and chemokines in fasting serum samples were determined using the Quantibody Inflammation Array. Compared with T2DM alone, patients with T2DM combined with PTB have higher fasting blood glucose levels and monocyte counts in circulation. Among the four groups, circulating IL-10 levels peaked in patients with T2DM and PTB (p<0.05). Univariate linear analysis showed that serum IL-10 levels were positively associated with myeloid cells but negatively correlated with lymphocyte counts in these patients (p<0.05). Serum IL-6 levels were 1.6-fold higher in patients with T2DM plus PTB than in those with T2DM alone. In conclusion, PTB infection in patients with T2DM had distinct inflammatory profiles and sustained hyperglycaemia compared with PTB or T2DM alone. IL-10 levels and elevated monocyte counts could be hallmarks of patients with T2DM infected with PTB.